2022
DOI: 10.1002/ijgo.14253
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differential metabolites using untargeted metabolomics between gestational diabetes and normal pregnant women

Abstract: Objective To study the metabonomics differences between pregnant women with gestational diabetes mellitus (GDM) in the third trimester and those in a group without GDM by screening a group of highly efficient and sensitive markers for GDM and validating previously published early metabolic markers of GDM. Methods A cross‐sectional cohort study based on ultra performance liquid chromatography tandem mass spectrometry untargeted metabolomics analysis of serum samples collected from 59 pregnant women with GDM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In recent years, many analyses have shown that metabolites during pregnancy are associated with various gestational disorders. Peng ML' study showed metabolic disorders were exhibited in gestational diabetes mellitus and 27 metabolites were identi ed as the differential metabolites [13] . A metabolomics study and meta-analysis showed that prenatal exposure to β-HCH and mecarbam could decrease the offspring's birth weight mainly by disrupting thyroid hormone metabolism and glyceraldehyde metabolism [14] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many analyses have shown that metabolites during pregnancy are associated with various gestational disorders. Peng ML' study showed metabolic disorders were exhibited in gestational diabetes mellitus and 27 metabolites were identi ed as the differential metabolites [13] . A metabolomics study and meta-analysis showed that prenatal exposure to β-HCH and mecarbam could decrease the offspring's birth weight mainly by disrupting thyroid hormone metabolism and glyceraldehyde metabolism [14] .…”
Section: Introductionmentioning
confidence: 99%